The Influence of Internal Organizational Communication on Economic and Green Management Efficiency in Electric Truck Utilization within Logistics Organization - Tanthaphaiboon, Bordin; Damnet, Anamai; Poo-udom, Aunchistha (Research Community and Social Development Journal, 2026)
Introduction: The logistics industry is an important mechanism driving the Thai economy. However, road transportation remains a major source of carbon dioxide emissions. The use of electric trucks is therefore an important approach to support green logistics and reduce energy costs. Nevertheless, the successful adoption of electric trucks requires internal organizational communication to create shared understanding among employees. This study aimed to analyze the influence of internal organizational communication on green management efficiency and economic efficiency. Methodology: This study employed a quantitative research design and collected data using a questionnaire. The sample consisted of 101 employees from a logistics organization in Thailand that had adopted electric trucks. The respondents were selected through purposive sampling. The questionnaire covered internal organizational communication, green management efficiency, and economic efficiency. Data were analyzed using descriptive statistics and Ordinal Logit Regression with a Hierarchical Regression approach. Results: The respondents reported a high level of agreement regarding internal organizational communication, green management efficiency, and economic efficiency. The Cronbach’s alpha coefficients of all three variables were at a high level. The analysis revealed that internal organizational communication had a statistically significant positive effect on green management efficiency and also had an indirect positive effect on economic efficiency through green management efficiency. Discussion: The findings indicated that achieving economic efficiency from the use of electric trucks required effective green management. Such green management was supported by internal communication that created shared understanding among employees with different roles and experiences. Suggestion: Logistics organization should establish electric truck policies that are linked to green management strategies, develop internal communication systems, and encourage feedback from operational employees. In addition, the government should support incentive measures, infrastructure development, and human resource development to accelerate the transition toward a low-carbon transportation system.